Defect‐Rich Copper‐doped Ruthenium Hollow Nanoparticles for Efficient Hydrogen Evolution Electrocatalysis in Alkaline Electrolyte. Issue 18 (21st August 2020) - Liang, Jiashun; Zhu, Lixing; Chen, Shaoqing; Priest, Cameron; Liu, Xuan; Wang, Hsing‐Lin; Wu, Gang; Li, Qing
Abstract: It is of great importance to develop highly eﬃcient and stable Pt‐free catalysts for electrochemical hydrogen generation from water electrolysis. Here, monodisperse 7.5 nm copper‐doped ruthenium hollow nanoparticles (NPs) with abundant defects and amorphous/crystalline hetero‐phases were prepared and employed as efficient hydrogen evolution electrocatalysts in alkaline electrolyte. Specifically, these NPs only require a low overpotential of 25 mV to achieve a current density of 10 mA cm −2 in 1.0 M KOH and show acceptable stability after 2000 potential cycles, which represents one of the best Ru‐based electrocatalysts for hydrogen evolution. Mechanism analysis indicates that Cu incorporation can modify the electronic structure of Ru shell, thereby optimizing the energy barrier for water adsorption and dissociation processes or H adsorption/desorption. Cu doping paired with the defect‐rich and highly open hollow structure of the NPs greatly enhances hydrogen evolution activity. Abstract : Monodisperse 7.5 nm Cu‐doped hollow Ru nanoparticles (NPs) with abundant defects were successfully prepared. The developed hollow Cu−Ru NPs demonstrate outstanding hydrogen evolution activity in an alkaline electrolyte. The enhanced activity can be ascribed to Cu incorporation and the defect‐rich hollow structures.